2016
DOI: 10.3389/fsurg.2016.00031
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Total Hip Replacement for the Management of Severe Developmental Dysplasia of the Hip in the Middle Eastern Population: A Prospective Analysis

Abstract: IntroductionIn the Middle East, severe developmental dysplasia of the hip with subsequent high dislocation is often seen. We assessed the efficiency of total hip replacement (THR) with subtrochanteric shortening femoral osteotomy and trochanteric advancement in this population.MethodsThis prospective study assessed 25 female patients with symptomatic and severe (Crowe IV). Pre- and postoperative Harris hip score (HHS) and Oxford hip score (OHS) were performed alongside assessment of leg length discrepancy (LLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This may be due to inappropriate road traffic and street and far from health care service. These findings were in the same line with Imam et al (2016) who clarified that, in a study about cement less Total Hip Replacement for the management of severe Developmental Dysplasia of the Hip in the Middle Eastern population; A prospective Analysis, at Egypt, more than half of the studied patients were life in rural area.…”
Section: Discussionsupporting
confidence: 86%
“…This may be due to inappropriate road traffic and street and far from health care service. These findings were in the same line with Imam et al (2016) who clarified that, in a study about cement less Total Hip Replacement for the management of severe Developmental Dysplasia of the Hip in the Middle Eastern population; A prospective Analysis, at Egypt, more than half of the studied patients were life in rural area.…”
Section: Discussionsupporting
confidence: 86%
“…Femoral shortening via proximal femoral osteotomy and greater trochanter distal advancement can be associated with significant complications, while they allow for preservation of abductor mechanism as well as more flexibility in correction of rotational deformities. Patients with Crowe Ⅳ dysplastic hips treated with subtrochanteric osteotomy and uncemented components show generally excellent healing rates of the osteotomy, while a 10-year follow-up study also revealed improved lasting Harris hip scores in patients with dysplasia treated with modular femoral components and subtrochanteric osteotomy [34,35].…”
Section: Discussionmentioning
confidence: 97%
“…[1] Moreover, the ability to sit cross-legged is one of the functional outcomes employed to evaluate patients after a total hip arthroplasty. [14] The study on the Indian population performing the cross-legged sitting posture found a mean abduction angle of 39º (19º-57º) and a mean external rotation angle of 49º (42º-58º). [10] That work found more hip abduction angles and fewer external rotation angles than our study.…”
Section: Discussionmentioning
confidence: 99%